Self-Acceptance Of Inmates In Terms Of Gender And Education Level - Sari, Rini Eka; Nugroho, Andhi Dwi; Ramadhan, Bayu Jati (Universitas Islam Negeri Raden Intan Lampung, 2024)
According to numerous views of self-acceptance, those who can accept themselves are aware of their traits and are not caught in anger, blaming others, or pitying themselves for their limitations. The goal of this study is to determine self-acceptance in inmates based on gender differences and level of education. The study hypothesizes differences in self-acceptance among inmates based on gender and educational level. This study involved 124 Class IIA Yogyakarta Correctional Facility inmates and Class IIB Women's Correctional Facility. The purposive sampling technique was employed to select the participants. The data collecting technique employed was a self-acceptance scale. The data analysis technique performed was the 2-way ANOVA. Hypothesis testing yielded a FoAB value of 0.991, with a significance level 0.000 (P <0.01). As a result, the study's hypothesis has been proven: there are differences in self-acceptance among inmates based on gender and education level. The researchers tested separately to see if there were differences in the self-acceptance of inmates based on gender and obtained a FoA value of 0.659 with a significance level of 0.000 (P < 0.01). There is no difference in self-acceptance based on education level where the FoB value is 0.000 with a significant level of 0.928 (P> 0.05).Keywords: Gender, Inmates, Self-Acceptance, Level of education